PENINGKATAN KOMPETENSI DIGITAL MARKETING SISWA SMK MELALUI MODEL WORKSHOP BERBASIS PRAKTIK PADA SMKN 1 BARRU - Aris Baharuddin; Mochtar Luthfi M; Syarifuddin Syarifuddin; Fatimah Akbal; Andhi Febisatria (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The rapid development of digital technology has transformed marketing practices and increased the need for adaptive digital marketing competencies among vocational students. SMKN 1 Barru faces challenges such as low practical digital literacy and limited structured training. The Entrepreneurship and Digital Marketing Training Program was designed to strengthen students’ skills in content creation, digital media management, and basic business planning. The results indicate improvements in students’ digital promotion abilities, creativity, and job readiness. The program also contributes to enhancing the school’s entrepreneurship ecosystem and supporting local economic empowerment through digital-based initiatives.